2017
DOI: 10.1248/bpb.b17-00160
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Curcumin on Manganese-Induced BV-2 Microglial Cell Death

Abstract: Curcumin, a bioactive component in tumeric, has been shown to exert antioxidant, anti-inflammatory, anticarcinogenic, hepatoprotective, and neuroprotective effects, but the effects of curcumin against manganese (Mn)-mediated neurotoxicity have not been studied. This study examined the protective effects of curcumin on Mn-induced cytotoxicity in BV-2 microglial cells. Curcumin (0.1-10 µM) dose-dependently prevented Mn (250 µM)-induced cell death. Mn-induced mitochondria-related apoptotic characteristics, such a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…Despite the hydrophilic nature of TA/MnP-PVPON, there is a reasonable concern about its cytotoxicity due to cationic pyridinium groups and manganese cations , of the MnP pendant groups which can be cytotoxic if released from PVPON. To examine the potential cytotoxic effects of TA/MnP-PVPON, we performed an MTT assay to assess the viability of splenocytes from NOD mice, a spontaneous mouse model of Type 1 diabetes, following a 48 h incubation with (PVPON/TA) 2 (MnP-PVPON/TA) 2 ­(PVPON/TA), and (PVPON/TA) 2 (MnP-PVPON/TA) 2 (PVPON/TA) 1.5 capsules, with (PVPON/TA) 5 and (PVPON/TA) 5.5 as negative cytotoxicity controls .…”
Section: Resultsmentioning
confidence: 99%
“…Despite the hydrophilic nature of TA/MnP-PVPON, there is a reasonable concern about its cytotoxicity due to cationic pyridinium groups and manganese cations , of the MnP pendant groups which can be cytotoxic if released from PVPON. To examine the potential cytotoxic effects of TA/MnP-PVPON, we performed an MTT assay to assess the viability of splenocytes from NOD mice, a spontaneous mouse model of Type 1 diabetes, following a 48 h incubation with (PVPON/TA) 2 (MnP-PVPON/TA) 2 ­(PVPON/TA), and (PVPON/TA) 2 (MnP-PVPON/TA) 2 (PVPON/TA) 1.5 capsules, with (PVPON/TA) 5 and (PVPON/TA) 5.5 as negative cytotoxicity controls .…”
Section: Resultsmentioning
confidence: 99%
“…Shin et al [61] reported that curcumin (200 mg/kg by intraperitoneal route (i.p.)) reduced kainic acid-induced seizures in mice through the increased expression of HO-1 and endothelial nitric oxide synthase (eNOS) in hippocampal astrocytes, whereas Park and Chun [62] demonstrated that curcumin (0.1–10 µM) reduces oxidative stress, apoptosis, and mitochondrial damage through the direct involvement of HO-1 in BV-2 microglial cells.…”
Section: Curcumin Neuroprotection and The Ho/bvr Pathwaymentioning
confidence: 99%
“…these results in mat be caused by the ability of curcumin to prevent GSH decrease, thus protecting the cell from caspase 3 activation and DNA fragmentation [38]. On the same line, [39] concluded downregulation of caspase 3 expression, as well as elevation of intracellular GSH level in manganese exposed microglial cells.…”
Section: Discussionmentioning
confidence: 95%